Wellcome Trust: antimicrobials and antimicrobial resistance - Armstrong, Thomas (2017)
The issue of antimicrobial resistance is one that threatens the very existence of humanity. For this reason it should be subject to increasingly intense investigation by the scientific community. The aims of this work was to explore two projects focused on creating novel treatments and therapies to be used as antimicrobial strategies. The first project was focused on the synthesis of novel anti-tuberculosis (TB) drugs, in order to address the increasing issue of multi and extensively drug-resistant TB. To this end, a partial synthesis of two iminosugar molecules was carried out, using a ring closing metathesis as a key step to form the desired 5-membered ring. A similar approach was taken to try and synthesise a furanose equivalent but this reaction was unsuccessful. These iminosugars have been shown to act as moderate inhibitors of the Galactofuranosyl Transferase 2 (GalfT2) pathway in Mycobacterium tuberculosis. Derivative structures of these iminosugars were proposed for future synthesis in order to explore the potential of iminosugars as GalfT2 inhibitor class. A concise synthesis of the biologically active cerebrosides compound KRN7000 is reported. This synthesis uses a TBAI mediated glycosylation step to deliver, exclusively, the desired α-galactoside. The synthesis of an azide-containing analogue was investigated but installation of the azide functionality via a Mitsunobu reaction proved unsuccessful. Two PTAD linkers were designed which could be attached to 6- deoxy-6-azido-α-GalCer in order to investigate further conjugation to the flagellin through the PTAD moiety. A partial synthesis of these PEG compounds is reported.